Effect of Initial Surface Finishing Roughness on Corrosion Behaviour of AISI 1050 Carbon Steel in CO2 Environment - Rumaizi, Shahril Ikhwan (2018)
There are different parameters which can affect electrochemical reactions such as type of electrolyte, velocity, temperature, oxidizing agents, impurities, anode material type and surface treatment. This research is purposely to investigate the factor that influence the corrosion rate focuses on the mechanistic aspect of the metal itself in term of initial surface finishing roughness which are essential to understand early-stage features of corrosion. Surface finishing roughness of the metal was believed could affect the hydrodynamic and mass transfer boundary layer which influenced electrochemical and mechanical-chemical behaviour on the surface of the metal. Two main type of testing were employed to get the corrosion rate of the tested metal which are Linear Polarization Resistance (LPR); to measure the average current density, icorr of the corrosion mechanism and Weight Loss Immersion; to measure the average weight loss of the metal due to corrosion. Corrosion rate values will be calculated based on the average current density, icorr and average weight loss and a trend in the effect of surface roughness on corrosion resistance of mild steel was introduced. The experiments used the samples which were abraded using silicon carbide, SiC abrasive paper grit #80, #280 and #500 respectively. The initial surface topography of the metal will be analyzed using Atomic Force Microscopy (AFM) to differentiate the average surface roughness of the surface. The specimen was tested at pH 5.5, 3.5 wt. % Sodium Chloride which react as synthetic seawater, in static flow solution purged with CO2 gas. The experimental results showed that as the surface finishing become finer, the average weight loss of the corroded sample decreased with average decrement about 11.78% and the average of the current density, icorr of the corrosion mechanism of the corroded sample decreased with average decrement about 10.46%. In summary, when the surface finishing become rougher, the corrosion activity of the metal increase based on the increment of average weight loss and current density, icorr values hence rate of the corrosion will increase respectively